2020
DOI: 10.1111/iej.13384
|View full text |Cite
|
Sign up to set email alerts
|

The impact of minimally invasive root canal preparation strategies on the ability to shape root canals of mandibular molars

Abstract: Lima CO, Barbosa AFA, Ferreira CM, Augusto CM, Sassone LM, Lopes RT, Fidel SR, Silva EJNL. The impact of minimally invasive root canal preparation strategies on the ability to shape root canals of mandibular molars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 52 publications
3
14
0
3
Order By: Relevance
“…The percentage of unprepared canal area was significantly greater in the UltraAC groups when compared to the TradAC groups. This result is in line with previous studies (Krishan et al 2014, Barbosa et al 2020, which reported higher values for unprepared areas in ConsAC groups in comparison with TradAC groups. Moreover, no difference was found between the instruments, indicating the ability of XP to expand and adapt to the root canal lumen, contacting more areas within the root canals, similar to instruments with greater tapers, such as Reciproc.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The percentage of unprepared canal area was significantly greater in the UltraAC groups when compared to the TradAC groups. This result is in line with previous studies (Krishan et al 2014, Barbosa et al 2020, which reported higher values for unprepared areas in ConsAC groups in comparison with TradAC groups. Moreover, no difference was found between the instruments, indicating the ability of XP to expand and adapt to the root canal lumen, contacting more areas within the root canals, similar to instruments with greater tapers, such as Reciproc.…”
Section: Discussionsupporting
confidence: 93%
“…Despite a lower percentage of dentine being removed in the UltraAC groups, the load capacity was similar between both access cavities and systems used for root canal preparation. This result is in line with previous studies that evaluated TradAC and minimally access modalities (Moore et al 2016, Rover et al 2017, Augusto et al 2020, Barbosa et al 2020, Silva et al 2020a. Nonetheless, a previous study (Saberi et al 2020) demonstrated greater load capacity in thermocycled mandibular molars with truss access cavities in comparison with TradAC.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…XP-endo Shaper (XPS; FKG Dent ire SA, La Chaux-de-Fonds, Switzerland) and M3-L (Yirui, China) are another two single-file systems, but operations in rotary movement. The XPS instrument takes on a snake-shaped form with a triangular cross-section, and combines the MaxWire alloy technology and the Booster tip with a six-blade tip (12,16,17,(19)(20)(21). M3-L is made of heat-treated alloy (M-wire), and has a double S-shape cross-section with 2 cutting flutes and a non-cutting tip (22).…”
Section: Introductionmentioning
confidence: 99%